The Concept of Concursus Realis in Criminal Law; A Legal Study of The Crimes of Rape and Murder - Seto Nugroho, Fajar; Ningtyas, Mega Ayu; Muljono, Bambang Eko; Hidayatullah, Ferdiansyah Safi’i (Universitas Islam Lamongan, 2025)
Concursus realis in cases of rape accompanied by murder based on the provisions of criminal law in Indonesia in Article 65 of the Criminal Code (KUHP) provides for one sentence for perpetrators who commit two independent crimes simultaneously but have never had a previous court decision. The research method used is a normative legal approach by analyzing laws and regulations and accountability for related cases. The results of the study indicate that the application of concursus realis allows perpetrators to be subject to one sentence with a maximum sentence and can be increased by one third of the heaviest sentence, as long as there is an element of intent, the ability to be legally responsible, and the absence of a valid excuse. This principle is important to ensure justice in sentencing, not only based on criminal acts, but also the awareness and will of the perpetrator when committing the crime. In addition, the study highlights the need for caution and thoroughness of law enforcement officers and judges in implementing this provision, especially in cases related to human rights violations that have existed since birth which must be protected and respected. In cases involving human rights, such as rape and murder, the application of the law must be based on the national legal system. It is hoped that the results of this study can provide academic and practical contributions in supporting the enforcement of concurrent criminal law in Indonesia, as well as being a consideration for law enforcement so that the judicial process runs fairly and effectively.